2010
DOI: 10.1111/j.1939-1676.2010.0640.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype Predicts Survival Time in Dogs with Chronic Lymphocytic Leukemia

Abstract: Background: Chronic lymphocytic leukemia (CLL) is a hematologic disorder in dogs, but studies on prognostic factors and clinical outcome are lacking. In people, several prognostic factors have been identified and currently are used to manage patients and determine therapy.Objectives: The aim of the study was to determine if the immunophenotype of neoplastic cells predicts survival in canine CLL.Design: Retrospective study. Animals: Forty-three dogs with CLL.Procedures: Records of dogs with a final diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 18 publications
2
76
3
Order By: Relevance
“…A CD44 mediated anti-apoptotic pathway has been demonstrated in human B-CLL (Fedorchenko et al, 2013), but the association between increased expression and prognosis is still undetermined (Fedorchenko et al, 2013 andHerishanu et al, 2011). Our results did not reveal any significant difference in CD44 MFI among different phenotypical subtypes which have been considered of prognostic value in dog (Comazzi et al, 2011), however a definitive conclusion may not be assessed due to the reduced number of cases for each subgroup. mRNA levels of the constant region of CD44, composed by exons 1-5, which encodes for the extracellular globular domain, and exons 16-20, which encodes for transmembrane region and cytoplasmic tail were also analyzed.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…A CD44 mediated anti-apoptotic pathway has been demonstrated in human B-CLL (Fedorchenko et al, 2013), but the association between increased expression and prognosis is still undetermined (Fedorchenko et al, 2013 andHerishanu et al, 2011). Our results did not reveal any significant difference in CD44 MFI among different phenotypical subtypes which have been considered of prognostic value in dog (Comazzi et al, 2011), however a definitive conclusion may not be assessed due to the reduced number of cases for each subgroup. mRNA levels of the constant region of CD44, composed by exons 1-5, which encodes for the extracellular globular domain, and exons 16-20, which encodes for transmembrane region and cytoplasmic tail were also analyzed.…”
Section: Resultscontrasting
confidence: 51%
“…However, both CLL and AL are poorly characterized in dogs and few pathogenic and prognostic studies are available in the literature , Comazzi et al, 2011and Usher et al, 2009. To the best of our knowledge, no information is present in the veterinary literature on the role of CD44 in canine hematopoietic tumors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Leifer et al reported that among 22 CLL cases, three dogs had second malignancies (two lymphosarcoma and one undifferentiated round cell sarcoma) [6]. Another publication reported that three dogs developed high-grade lymphoma (two B-CLL dogs progressed to high-grade B-cell lymphoma, and one T-CLL dog progressed to high-grade T-cell lymphoma) among 43 CLL cases [3]. However, the clinical details and outcome of the disease were not included in these reports, causing the lack of information of this phenomenon in our canine counterparts.…”
mentioning
confidence: 99%
“…It was possible that our patient first developed T-cell CLL, followed by highgrade B-cell lymphoma as a second malignancy. Moreover, the survival duration of our patient was relatively short (194 days) compared with the survival of dogs with common high-grade B-cell multicentric canine lymphoma treated using the L-VCA short protocol (median survival duration, 396 days [17]) or T-cell CLL (median overall survival time, 930 days [3]). …”
mentioning
confidence: 99%